Solving for a variable in terms of other variable Solve for \( Z \). \( X=\frac{5}{6}(Y-Z) \) \( Z=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve for \( Z \), you'll want to isolate it on one side of the equation. Start with \( X = \frac{5}{6}(Y - Z) \). Multiply both sides by \( \frac{6}{5} \) to eliminate the fraction: \[ \frac{6}{5}X = Y - Z. \] Now, to isolate \( Z \), simply rearrange the equation: \[ Z = Y - \frac{6}{5}X. \] And there you have it! \( Z = Y - \frac{6}{5}X \). Keep in mind that rearranging equations is like a puzzle; always double-check your operations to ensure every piece fits perfectly!